2014
DOI: 10.1093/geront/gnu004
|View full text |Cite
|
Sign up to set email alerts
|

Older Chinese Immigrants’ Relationships With Their Children: A Literature Review From a Solidarity–Conflict Perspective

Abstract: This review suggests that although filial piety continues to influence older parent-child relationship in Chinese immigrant families, many changes have occurred. These findings have important implications for service planning and delivery for this cultural group. This review also provides evidence for the utility of the solidarity-conflict model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 44 publications
4
59
0
Order By: Relevance
“…The review found that although the GAI has been translated into Chinese and used with older Chinese people living in mainland China (Lin et al ., ), it has not been used with older Chinese immigrants. There were also very limited data on anxiety among older Chinese immigrants, with only one unpublished report being identified.…”
Section: Discussionmentioning
confidence: 57%
“…The review found that although the GAI has been translated into Chinese and used with older Chinese people living in mainland China (Lin et al ., ), it has not been used with older Chinese immigrants. There were also very limited data on anxiety among older Chinese immigrants, with only one unpublished report being identified.…”
Section: Discussionmentioning
confidence: 57%
“…A systematic review by Lin, Bryant, Boldero, and Dow (2015) used search terms of Chinese, older adults, family relationships, filial piety, and conflicts to explore the relationship between Chinese parents and children and concluded that intergenerational differences exist in traditional values and beliefs. These conflicts and confusion between generations may hinder honest communication of ACP among Chinese family members.…”
Section: Intergeneration Differences and Acp In Chinese Americansmentioning
confidence: 99%
“…Qualitative findings throughout these articles illuminated pertinent issues affecting some reunified Asian families in New Zealand, such as heightened family tensions and dissatisfaction with living arrangements . A possible reason behind the impact of suboptimal family relationships on older Chinese immigrants is their higher level of filial expectations, when compared to older Caucasians . The international literature indicates altered family relationships between older Chinese immigrants and their adult children, in the United States (US), United Kingdom (UK), Australia and Canada .…”
Section: Discussionmentioning
confidence: 98%
“…A possible reason behind the impact of suboptimal family relationships on older Chinese immigrants is their higher level of filial expectations, when compared to older Caucasians . The international literature indicates altered family relationships between older Chinese immigrants and their adult children, in the United States (US), United Kingdom (UK), Australia and Canada . Nevertheless, studies showed that older Asian immigrants’ relationships with their adult children can become more harmonious, provided acculturative adjustments are made upon relocation …”
Section: Discussionmentioning
confidence: 99%